Chapter La buona fama di un falsario: eruditi, critici e luoghi nel Piemonte del Settecento - Provero, Luigi (Reti Medievali E-Book, 2021)
Giuseppe Francesco Meyranesio (1729-1793) is well known for the ancient and medieval texts he produced and disseminated, the falsity of which has been widely proved. This essay aims to reread his story from another point of view, namely the network of relationships and correspondents set up by Meyranesio, a network that allows us to understand the reasons for his forgeries, which were an attempt - substantially successful - to build a good reputation in front of the main subalpine scholars, but also - and here Meyranesio failed - to obtain a benefit that freed him from pastoral tasks and allowed him to devote himself full time to study.